Strengthening the Integration of Nationalist Jihad and Ecotheology Values in Religious Moderation and Ecotheology Literacy for Santri (Islamic Boarding School Students) - Syamsu Nahar; AI Wati; Abdi Mubarak Syam; Faiza Adinda; Nur Aisyah Panjaitan; Zahrani Nabila; Putri Safira; Putra Apriadi Siregar; Muhammad Rezebri; Sri Rahayu (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
This community service program aimed to strengthen the literacy of santri (Islamic boarding school students) in religious moderation by integrating the core values of contextual jihad, inclusive nationalism, and ecotheology. The urgent need to fortify the younger generation's resilience against religious extremism, radicalism, and environmental apathy drove the initiative. The program employed a participatory action research method in Langsa City, focusing on the formation and training of cadres who acted as peer educators. A single-group pretest and posttest design involving 30 santri was used to measure changes in ecotheological practices and attitudes towards religious moderation and nationalism. The results demonstrated a highly significant increase in the santri's ecotheological practices (p < 0.001), evidenced by improved habits in water conservation, waste management, and use of reusable items. Furthermore, a significant strengthening was observed in their commitment to religious moderation and nationalism (p = 0.006), including stronger support for the rights of minorities, the Indonesian constitution (UUD 1945), and Pancasila. The study concludes that the peer-educator-based mentoring model is an effective strategy for simultaneously internalizing the integrative values of constructive jihad, nationalism, and environmental stewardship. This integrative approach offers a sustainable model for developing a generation that is religious, patriotic, and ecologically conscious, which can be replicated in other Islamic educational institutions. Keywords: Religious Moderation, Ecotheology, Jihad, Nationalism, Santri, Peer Educator.